Development of integral economics in countries, regions and cities - Kovalevskiy, Georgiy; Grynenko, Volodymyr; Krasnokutska, Yulia (Харківський національний автомобільно-дорожній університет, 2014)
The integral economics is named the economics of a man. A (man) human being, satisfaction of her/his rights and necessities, increase of welfare, quality and duration of life is the main figure in the integral economics of man. The task is of the research is to determine principles of this new type of economics in which to improve the quality and length of life of each person are integrated, that is, extended to the new, higher level, as soon as possible all the achievements of science and practice around the world. There are two absolutely new methods offered in this paper - method of balances of indexes-indicators and the method of the integral system; The new concepts and methods of integral economics of man have been developed in this paper first time: integral systems of development of a human being, the balance of indicators of economic and social development of a human being. Every without exception major factor of development of integral economics of man has been integrated firstly in the integral systems, in integral balances of indicator: human factors, productivity, financial, manager's and informative factors, factors of economic freedom, scientific and technical advance, consumer demand and supply, factors of quality of life, number of lives and life time of a human being. The developed systems can be applied on any level – international, national or on a micro level.
Keywords: integral economics; integral balаnces of indicators; economic development; social development; integral development of a human being; 330.1+168.522